Integrating Psychosocial and Structural Resources: The Role of Work-Life Balance and Technology Readiness in Employee Engagement - Dewana Ananda Agsa; Ade Solahudin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the role of work-life balance and technology readiness in improving employee engagement among PNM employees in the Cirebon region. The study employed a quantitative explanatory approach with a survey method involving 100 respondents selected through purposive sampling, specifically employees actively involved in technology-based work. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), including evaluation of the measurement model and the structural model. The results showed that work-life balance had a positive and significant effect on employee engagement (β = 0.419; p < 0.05), while technology readiness had a more dominant influence (β = 0.470; p < 0.05). The R² value of 0.741 indicates that both variables explain 74.1% of the variation in employee engagement. Effect size (f²) analysis demonstrated a strong contribution from both variables. The novelty of this research lies in the integration of work-life balance as a psychosocial resource and technology readiness as a structural resource within the Job Demands-Resources (JD-R) framework. Theoretically, this research enriches human resource management studies, while practically it provides implications for microfinance institutions to strengthen work-life balance policies and digital competencies to increase employee engagement.